Change on Regional Labor Markets in Poland in Years 2006–2009 - Zieliński, Mariusz; Jonek-Kowalska, Izabela (Regional Barometer. Analyses & Prognoses, 2012)
The article concerns changes taking place in the regional labor market in Poland under the influence of the economic crisis. Statistical analysis is based on data published by GUS and includes: employment and unemployment change levels in years 2006–2009 in Poland, and the sector level and the structure of employment in regional labor markets. On the basis of statistical data regarding employment, the regions were determined which were distinguished positively in view of the whole country, in terms of processes advancement of employment structure changes in the direction specific for the post-industrial period. This confirms the thesis that more developed and diversified regions, according to economic base, cope better in the conditions of an economic crisis. In consequence, this leads to situation deterioration of differentiation in regional labor markets.